Proteomic Analysis of Differentially Expressed Proteins Involved in Peel Senescence in Harvested Mandarin Fruit - Li, Taotao; Zhang, Jingying; Zhu, Hong; Qu, Hongxia; You, Shulin; Duan, Xuewu; Jiang, Yueming (Frontiers in Plant Science, 2016)
Mandarin (Citrus reticulata), a non-climacteric fruit, is an economically important fruit worldwide. The mechanism underlying senescence of non-climacteric fruit is poorly understood. In this study, a gel-based proteomic study followed by LC-ESI-MS/MS analysis was carried out to investigate the proteomic changes involved in peel senescence in harvested mandarin ‘Shatangju’ fruit stored for 18 d. Over the course of the storage period, the fruit gradually senesced, accompanied by a decreased respiration rate and increased chlorophyll degradation and disruption of membrane integrity. Sixty-three proteins spots that showed significant differences in abundance were identified. The up-regulated proteins were mainly associated with cell wall degradation, lipid degradation, protein degradation, senescence-related transcription factors, and transcription-related proteins. In contrast, most proteins associated with ATP synthesis and scavenging of reactive oxygen species were significantly down-regulated during peel senescence. Three thioredoxin proteins and three Ca2+ signaling-related proteins were significantly up-regulated during peel senescence. It is suggested that mandarin peel senescence is associated with energy supply efficiency, decreased antioxidant capability, and increased protein and lipid degradation. In addition, activation of Ca2+ signaling and transcription factors might be involved in cell wall degradation and primary or secondary metabolism.